The clinical value of short-term insemination: a retrospective analysis of 3496 patients - Xinyue Zhang; Yufeng Wang; Jihong Yang; Yangbai Li; Yao Chen; Yingying Yang; Ting Feng; Suying Li; Li Chen; Yun Qian (BMC Pregnancy and Childbirth)
Abstract Background The safety and effectiveness of short-term insemination remain a subject of controversy. This study aims to investigate the impact of short-term insemination on both embryo quality and pregnancy outcomes and whether it is necessary to apply short-term insemination to all patients underwent in vitro fertilization (IVF). Methods A retrospective analysis was conducted on 3,496 patients from two centers over the period January 2016 to December 2022. Of these, 1307 patients underwent IVF, 1656 patients were treated with short-term IVF, 166 patients received early rescue intracytoplasmic sperm injection (R-ICSI) and 367 patients were treated with ICSI. The clinical and neonatal outcomes were compared between the two groups. Results The rate of high-quality embryos was significantly lower in the short-term IVF group compared to the routine IVF group (59.89% vs. 68.16%) (P = 0.000), the rate of blastocyst formation was significantly lower in the short-term IVF group compared to the routine IVF group (44.99% vs. 61.34%) (P = 0.000). There were no significant differences in clinical outcomes or neonatal outcomes between the two groups, irrespective of whether fresh or frozen embryos were used (both P > 0.05). The incidence of ≥ 3PN demonstrated no significant difference between the early R-ICSI and ICSI groups (1.04% vs. 0.66%) (P = 0.114), furthermore, the clinical outcomes were similar in both groups, for both fresh and frozen embryos (both P > 0.05). Conclusions For patients with primary fertility, short-term IVF combined with early R-ICSI can effectively prevent potential low fertilization or fertilization failure, reduce the risk of patients with no transferable embryo, avoid the waste of resources and had no adverse effects on neonatal outcomes. However, short-term IVF reduced the oocytes utilization rate in one single oocyte pick-up cycle, for patients with no risk factors for fertilization failure, the overnight fertilization is still one of the most important ways of insemination worthy of affirmation. Trial registration NA.